2011
DOI: 10.4062/biomolther.2011.19.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Thujopsis dolobrata Suppresses Atopic Dermatitis-Like Skin Lesions in NC/Nga Mice

Abstract: Atopic dermatitis (AD) is a multifactorial allergic infl ammatory skin disorder characterized by pruritic and eczematoid skin lesions. AD is commonly present in early infancy and childhood, although it can occur later in life and persist into adulthood (Barker et al., 2007;Brenninkmeijer et al., 2009). It results from interactions between susceptibility genes, the host's environment, skin barrier defects, bacterial and viral skin infections, and immunological factors (Leung and Bieber, 2003). Recent immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Interestingly, this compound significantly suppressed the expression of IL-6 mRNA, a major cytokine involved in skin inflammation [33], as determined by quantitative (Figure 2(a), left panel) or semiquantitative (Figure 2(a), right panel) RT-PCR. Under the conditions, however, up to 30  μ M of lutein exhibited no cytotoxic activity in RAW264.7 cells (Figure 2(d) left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this compound significantly suppressed the expression of IL-6 mRNA, a major cytokine involved in skin inflammation [33], as determined by quantitative (Figure 2(a), left panel) or semiquantitative (Figure 2(a), right panel) RT-PCR. Under the conditions, however, up to 30  μ M of lutein exhibited no cytotoxic activity in RAW264.7 cells (Figure 2(d) left panel).…”
Section: Resultsmentioning
confidence: 99%
“…27) In our previous study, it was reported that essential oil from Thujopsis dolobrata reduced both serum levels of histamine and IgE in atopic dermatitis (AD)-like skin lesions induced by 2,4-dinitrochlorobenzene (DNCB) in NC/Nga mice, and furthermore it presented a mast cell stabilizing effect by inhibiting the release of β-hexosaminidase from antigen-induced RBL-2H3 mast cells. 29) In present study, two compounds, (−)-elema-1,3,11(13)-trien-12-ol (1) and thujopsene (2) isolated from essential oil of Thujopsis dolabrata were investigated for the inhibition of mast cell degranulation, IL-4 secretion, and IL-4 mRNA and protein expression in antigen-induced RBL-2H3 mast cells. Extraction and Isolation The wood part of Thujopsis dolabrata (10 kg) was steam distilled for 3 h using a Clevengertype apparatus, yielding 141 g of essential oil.…”
mentioning
confidence: 99%
“…Sesquiterpenes 1, 5, and 8-11 exhibited potent antibacterial activity, and β-thujaplicin (12, hinokitiol) showed a broad spectrum of antibacterial and antifungal activity. Since the essential oil from T. dolabrata reduces atopic dermatitis (AD)-like skin lesions by inhibiting the production of IgE and histamine (Nam et al, 2011), studies on the antiallergic effects of the isolated compounds in mice are in progress, together with studies on the anti-AD mechanisms of these compounds.…”
Section: Antimicrobial Activity Of Compounds 1-15mentioning
confidence: 99%
“…Among them, hinokitiol (β-thujaplicin), the major component of this plant, has been found to show a broad spectrum of biological activities, including antimicrobial activity (Morita et al, 2003(Morita et al, , 2004, insecticidal effects, phytogrowth-inhibitory activity (Sakagami et al, 2000), cytotoxic effects on mammalian tumor cells (Inamori et al, 1993), and enzyme inhibitory activities such as those on catechol-O-methyltransferase and metalloproteases (Borchardt, 1973;Inamori et al, 1999). In a previous work (Nam et al, 2011), we had reported the effects of essential oil from T. dolabrata onatopic dermatitis (AD)-like skin lesions in NC/Nga mice. Our data indicated that the essential oil from T. dolabrata reduces AD-like skin lesions by inhibiting the production of IgE and histamine, and, thus IgE-mediated degranulation.…”
Section: Introductionmentioning
confidence: 98%